Secondary metabolites with medicinal activity extracted from fungi found in Central America - Arce-Torres, Luis Felipe (2020)
There´s a wide diversity of fungi that have medicinal activity in Central America, from which the secondary metabolites responsible for that activity can be extracted in order to treat various diseases. In this review, six different fungi with the potential to treat physical disorders were studied: Penicillium chrysogenum (P. chrysogenum), Ganoderma lucidum (G. lucidum), Trametes versicolor (T. versicolor), Schizophyllum commune (S. commune), Pleurotus mutilus (P. mutilus), Lentinula edodes (L. edodes), and one hallucinogenic mushroom useful in the field of mental health issues: P. cubensis. The secondary metabolites of greatest importance were penicillin and tiamulin as antibiotics, triterpenes with anticarcinogenic activity, various polysaccharides with antioxidant and antiparasitic activity, immune boosting and cholesterol regulating properties. Additionally, the hallucinogen psilocybin and its potential in psychotherapy treatments was also studied.